MUCH MORE THAN HONEY: BEES FROM URUGUAY. SCIENTIFIC COMMUNICATION FOR CHILDREN (Boletín de la Sociedad Zoológica del Uruguay, 2025)
When we face science communication, the strategies to cover child audiences are a great challenge. In 2020, a group of five female researchers studying bees at different research institutions in Uruguay decided to create a book on Uruguayan bees. Its objective was to promote their valuation, their essential role in natural ecosystems, and to raise their awareness. Thanks to the collaborative work, we generated a disclosure tool of 83 color pages with information on Uruguayan bee species, for which there was no accessible material for the general audience in our country. Fifty illustrative sheets of scientific concepts and information on bee biodiversity were generated, with 30 proposals for games and activities to paint, complete, interpret, and search for. Furthermore, thanks to the collaboration of different institutions and individuals, since 2022, more than 8,500 books have been distributed free of charge in 238 educational centers and to more than 420 private individuals in the 19 provinces of Uruguay. This project has promoted the visibility of a group of organisms with an essential activity in nature, in a non-traditional format to awaken the love for science and nature in future generations.
Keywords: Scientific communication; bees; pollination; biodiversity; children